Genes and cigarette smoking. - Munafò, MR; Johnstone, E (2008)
AIMS: Attempts to further our understanding of the determinants of cigarette smoking, tobacco addiction and related behaviours have included the dissection of genetic influences on these phenotypes. This review summarizes the current state of evidence from both twin and adoption studies and molecular genetic studies. We also review future research horizons and the direction which studies of this kind are likely to take in the near future. FINDINGS: There is consistent evidence from twin and adoption studies that genetic factors play a role in the aetiology of cigarette smoking. Nevertheless, despite a large number of candidate gene studies, and a smaller number of linkage studies, few reported associations and chromosomal regions of interest have proved to replicate reliably. This is due most probably to the small effects of individual loci on complex behaviours such as smoking. CONCLUSIONS: Future research is likely to include the study of gene x environment interactions (including gene x treatment interactions, which offer the prospect of genetically tailored smoking cessation treatment) and the use of more sophisticated smoking-related phenotypes, such as longitudinal smoking trajectories, and intermediate phenotypes which use technologies such as neuroimaging and other laboratory and biobehavioural measures.